BOUNDARY LAYER FLOW AND HEAT TRANSFER WITH VARIABLE VISCOSITY IN THE PRESENCE OF MAGNETIC FIELD - O.A, Ajala; L. O, Aseelebe; Z. O, Ogunwobi (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
A steady two dimensional boundary layer flow and heat transfer with variable viscosity electrically conducting fluid at T in the presence of magnetic fields and thermal radiation was considered. The governing equations which are partial differential equations were transformed into ordinary differential equations using similarity variables, and the resulting coupled ordinary differential equations were solved using collocation method in MAPLE 18. The velocity and temperature profiles were studied graphically for different physical parameters. The effects of the parameters on velocity and temperature profile were showed.